Técnica de aquisição de frequência alternada inspirada no sensor de linha lateral dos peixes para melhorar o imageamento sísmico - Silva, Francisco Wilton de Freitas (2020)
The bioengineering studies the principles of biological systems. It is a field that has inspired the development of several technologies that take part of our world. In this work we use concepts from the fish lateral line sensing mechanism and apply them to the processing of seismic images. The lateral line is a sensory system composed by an integrated set of mechanical sensors spanning along the fish body. We made a parallel with the geophysics exploration in which it is usual to employ an array of equally spaced identical mechanical sensors on theearth surface. In both situation the mechanical sensors capture and process mechanical vibrations from the environment to produce useful information. We explore the strategy that is called low-pass and high-pass sensors schema of fish lateral line in the geophysics exploration technique. We use the full wave inversion method to compare the conventional acquisition procedure of identical sensors with the alternative set of different sensors which mimics the fish lateral line. Our results show that the alternate sensors arrangement surpasses the conventional acquisition using just half of input information. The results pointed out that the image process technique is more efficient and economical than the costly usual seismic processing.